PERAN MASYARAKAT DALAM PENCEGAHAN DAN PENANGGULANGAN TERHADAP PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOTIKA - Gunawan Antiprawiro (Sociae Polites, 2014)
AbstractThe purpose of this research is to understand thepeoples’ response toward rampaging of narcoticmisuse in Yogyakarta and the existence ofpeoples’ participation of Yogyakarta. Based ondescriptive analysis of data collection throughsome techniques of (a) documentation study, (b)in-depth interview, (c) observation and (d)focused group discussion (FGD) it is exploredthat peoples’ participation has functioned associal energy and has developed as a socialmovement. Values which is rooted from variousresources like religions, ethics and regulation arethe important determinant and binding thepeople’s behavior to achieve success in theimplementation of P4GN (Prevention andElimination of Illegal Circulation and Misuse ofNarcotics). This social movement also showsconsistency and responsibility of the Republic ofIndonesia as a state toward the ASEANagreement and nations in the world to fightagainst misuse and illegal circulation ofnarcotics. The agreement of ASEAN has providedgreat opportunity for the youth and student inthe ASEAN’s countries to exchange information,to do comparative study and workshop amongthe young generation for the implementation ofP4GN.Keywords: People’s role, Elimination, MisuseNarcotics AbstrakTujuan penelitian ini adalah untuk mengetahuirespon masyarakat terhadap maraknyapenyalahgunaan narkotika di Yogyakarta, daneksistensi partisipasi masyarakat Yogyakarta.Dari analisis deskriptif terhadap data yangdihimpun dengan teknik : (a) studi dokumentasi,(b) wawancara mendalam, (c) observasi, dan (d)diskusi kelompok terarah (FGD) terungkap bahwapartisipasi masyarakat telah berfungsi sebagaienergi sosial dan berkembang sebagai suatugerakan sosial. Nilai dari berbagai agama, etika,serta Peraturan Perundangan merupakandeterminan penting dan mengikat perilakumasyarakat untuk mencapai keberhasilanpenyelengaraan P4GN. Gerakan sosial inimenunjukkan konsistensi danpertanggungjawaban Negara RepublikIndonesia atas kesepakatan ASEAN dan bangsabangsa dunia dalam memerangipenyalahgunaan dan peredaran gelapnarkotika. Kesepakatan Komunitas ASEANmemberikan peluang besar bagi pemuda danmahasiswa di negara negara ASEAN untuksaling tukar informasi, studi banding, danworkshop antar pemuda dan mahasiswa dalampenyelenggaraan P4GN.Kata Kunci: Peran Masyarakat,Penanggulangan, Penyalahgunaan Narkotika